The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.jdsr.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of the dental formula from the National Database of Health Insurance Claims and Specific Health Checkups of Japan

Abstract: The National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) is a database including health insurance claim and specific health checkup data. Observational studies using real-world big data attract attention because they have certain strengths, including external validity and a large sample size. This review focused on research using the dental formula of the NDB because the number of teeth is an important indicator of oral health. The number of teeth present calculated using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Of the 290 articles identified by the initial search, 248 were excluded after examining their title and abstract. Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 290 articles identified by the initial search, 248 were excluded after examining their title and abstract. Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of academic hospital patients, the mean difference was 1.0 teeth when the number of teeth assessed from the dental claims data was compared with that from radiographs [ 6 ], and this result was consistent with ours. In contrast, an ecological study based on claims-based assessment using a national database and summary results of a national survey in Japan [ 7 ] reported larger differences in the mean number of teeth among the older population. This difference to our findings may be partially explained by the tendency of the number of teeth in claims-based assessments to differ from the actual number of teeth in individuals with fewer teeth, such as older adults.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is potential for the number of teeth to be efficiently assessed using claims data, the use of claims-based assessment is limited, perhaps because its validity has not been sufficiently established. Several studies have reported the validity of the number of remaining teeth in dental claims data [ 6 , 7 ]; however, these studies were limited to patients in one hospital [ 6 ] or to assessments at the population level [ 7 ], rather than at the individual level. Therefore, it remains unclear whether the number of remaining teeth in dental claims data is valid for the general population if assessed using individual-level data.…”
Section: Introductionmentioning
confidence: 99%
“…The mission of the Council of Japan Dental Science of Societies (CJDSS) is to improve the operation of the social insurance system in the field of dental care, to collect and disseminate information related to dental care, and to cultivate and train dental professionals such as dentists and dental hygienists to develop and improve dental care [8] , [9] . Misuse of the medical reimbursement system may lead to issues such as increased medical expenses, greater medical disparities, decreased medical standards, and physician shortages.…”
Section: Introductionmentioning
confidence: 99%